Thermoresponsive Copolymer Nanovectors Improve the Bioavailability of Retrograde Inhibitors in the Treatment of Leishmania Infections - Craig, Evan; Calarco, Anna; Conte, Raffaele; Ambrogi, Veronica; d’Ayala, Giovanna Gomez; Alabi, Philip; Sello, Jason K.; Cerruti, Pierfrancesco; Kima, Peter E. (Frontiers in Cellular and Infection Microbiology, 2021)
Clinical manifestations of leishmaniasis range from self-healing, cutaneous lesions to fatal infections of the viscera. With no preventative Leishmania vaccine available, the frontline option against leishmaniasis is chemotherapy. Unfortunately, currently available anti-Leishmania drugs face several obstacles, including toxicity that limits dosing and emergent drug resistant strains in endemic regions. It is, therefore, imperative that more effective drug formulations with decreased toxicity profiles are developed. Previous studies had shown that 2-(((5-Methyl-2-thienyl)methylene)amino)-N-phenylbenzamide (also called Retro-2) has efficacy against Leishmania infections. Structure–activity relationship (SAR) analogs of Retro-2, using the dihydroquinazolinone (DHQZ) base structure, were subsequently described that are more efficacious than Retro-2. However, considering the hydrophobic nature of these compounds that limits their solubility and uptake, the current studies were initiated to determine whether the solubility of Retro-2 and its SAR analogs could be enhanced through encapsulation in amphiphilic polymer nanoparticles. We evaluated encapsulation of these compounds in the amphiphilic, thermoresponsive oligo(ethylene glycol) methacrylate-co-pentafluorostyrene (PFG30) copolymer that forms nanoparticle aggregates upon heating past temperatures of 30°C. The hydrophobic tracer, coumarin 6, was used to evaluate uptake of a hydrophobic molecule into PFG30 aggregates. Mass spectrometry analysis showed considerably greater delivery of encapsulated DHQZ analogs into infected cells and more rapid shrinkage of L. amazonensis communal vacuoles. Moreover, encapsulation in PFG30 augmented the efficacy of Retro-2 and its SAR analogs to clear both L. amazonensis and L. donovani infections. These studies demonstrate that encapsulation of compounds in PFG30 is a viable approach to dramatically increase bioavailability and efficacy of anti-Leishmania compounds.